A novel rapid screening method for health monitoring of building structures from earthquake records. Issue 16 (December 2019) - Lin, Ging-Long; Wang, Jer-Fu; Lin, Chi-Chang; Lin, Jim
This study presents a rapid screening method for health monitoring of building structures based on earthquake records. Compared with conventional damage detection techniques, the rapid screening system with few sensors is more attractive and cost-effective in assessing the global behaviors of a building structure. Only two tri-axial accelerometers are required for a building. One is mounted at the ground level, and another one is mounted at the top floor. First, the relative displacement of top floor to ground is calculated by on-line integration. Then, the diagram of absolute acceleration versus relative displacement of top floor is used to determine the pseudo stiffness of the whole building by linear regression. The decrease of pseudo stiffness denotes the occurrence and degree of damage in the building. A novel real-time damage technique is also proposed to detect nonlinear behavior of a building. A five-story shear-type building under earthquake excitations was illustrated for sensitivity analysis of pseudo stiffness considering different damage cases. Shaking-table-test data of a three-story benchmark building were used to verify the accuracy of the proposed damage assessment technique. In addition, the proposed method was also applied to evaluate a new eight-story residential building equipped with accelerometers in Taipei, Taiwan. Finally, the acceleration response records of a real building, which experienced moderate damages caused by the main shock of 1999 Taiwan Chi-Chi earthquake ( ML = 7.3), were considered to examine the applicability of the proposed method to generate a real-time damage indicator for a building with nonlinear behavior. All of the results show that the proposed method is reliable and effective for rapid diagnosis of building health.